2004
DOI: 10.1002/chin.200445007
|View full text |Cite
|
Sign up to set email alerts
|

Columbite‐Type FexMn1‐xNb2O6 Solid Solution: Structural and Magnetic Characterization.

Abstract: 0.25, 0.50, 0.75, and 1 are characterized by powder XRD, EPR, and magnetization measurements. The powder XRD patterns of all samples are indexed in space group Pbcn. The Fe and/or Mn cations are randomly distributed over the A-octahedral sites of the structure and there is no cation disorder between the A and Nb sites. The oxidation state of Fe and Mn is always +2. An antiferromagnetic transition is observed only for the two endmembers FeNb2O6 and MnNb2O6. -(TEALDI, C.; MOZZATI, M. C.; MALAVASI*, L.; CIABATTON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…28 Metavanadate MeV 2 O 6 (Me = divalent metal ions) compounds at normal pressures have the brannerite structure and a rich variety of possible polymorphs that are dependent on pressure and temperature, that is, orthorhombic columbite (Pbcn), 29 tetragonal trirutile (P4 2 /mmm), and trigonal PbSb 2 O 6 (P3̅ 1m) structures have been reported. 30 Beck 31 developed the coordination number rule and the rule of hardness to rationalize inorganic coordination structures and the available structures for the compounds with AB 2 O 6 stoichiometry, as occurs in ZnV 2 O 6 , and this author proposes the following polymorphs: CaAs 2 O 6 (P321), 32 FeNb 2 O 6 (Pbcn), 33 CaV 2 O 6 (C2/m), 34 SrV 2 O 6 (Pnma), 35 BaV 2 O 6 (C222), 36 HgV 2 O 6 (Pbca) 37 NiV 2 O 6 , (P1̅ ), 38 MoLa 2 O 6 (I4̅ 2m), 39 ThTi 2 O 6 (C2/c), 40 and ThTi 2 O 6 (C2/m). 41 ZnV 2 O 6 is a representative member of the AB 2 O 6 family 30 and has been studied intensively because of its technological importance, and very recently Butt et al 42 and Sun et al 43 reported large-scale synthesis of ZnV 2 O 6 nanostructures, highlighting its potential as a material for energy storage/ conversion.…”
Section: Introductionmentioning
confidence: 99%
“…28 Metavanadate MeV 2 O 6 (Me = divalent metal ions) compounds at normal pressures have the brannerite structure and a rich variety of possible polymorphs that are dependent on pressure and temperature, that is, orthorhombic columbite (Pbcn), 29 tetragonal trirutile (P4 2 /mmm), and trigonal PbSb 2 O 6 (P3̅ 1m) structures have been reported. 30 Beck 31 developed the coordination number rule and the rule of hardness to rationalize inorganic coordination structures and the available structures for the compounds with AB 2 O 6 stoichiometry, as occurs in ZnV 2 O 6 , and this author proposes the following polymorphs: CaAs 2 O 6 (P321), 32 FeNb 2 O 6 (Pbcn), 33 CaV 2 O 6 (C2/m), 34 SrV 2 O 6 (Pnma), 35 BaV 2 O 6 (C222), 36 HgV 2 O 6 (Pbca) 37 NiV 2 O 6 , (P1̅ ), 38 MoLa 2 O 6 (I4̅ 2m), 39 ThTi 2 O 6 (C2/c), 40 and ThTi 2 O 6 (C2/m). 41 ZnV 2 O 6 is a representative member of the AB 2 O 6 family 30 and has been studied intensively because of its technological importance, and very recently Butt et al 42 and Sun et al 43 reported large-scale synthesis of ZnV 2 O 6 nanostructures, highlighting its potential as a material for energy storage/ conversion.…”
Section: Introductionmentioning
confidence: 99%